Preparation of Y--Ba--Cu--O Superconductors by Chemical Solution Processes - Murakami, H; Nishino, J; Yaegashi, S; Shiohara, Y (Nihon Seramikkusu Kyōkai gakujutsu ronbunshi, 1990)
The characteristics of three chemical solution processes, evaporation and spray pyrolysis method, co-precipitation method and sol--gel method, were discussed in the preparation of raw materials for Y--Ba--Cu--O superconductors. There were two ways to produce superconductors: one involves the formation of barium carbonate in the course of producing superconductors, while the other does not. In the latter path, the temperature to form superconductors is approx 200 deg C lower than in the former. To prevent formation of barium carbonate, it is important that barium nitrates or their similar salts are used as precursors. Synthesis of 123 and 124 by the sol--gel method at low temperatures demonstrated the following points concerning the formation and phase stability of these superconductors. At lower temperatures, 124 is more stable than tetragonal 123. Orthorhombic 123 is a meta-stable phase and is produced through tetragonal 123 formed at temperature high enough to transform to orthorhombic phase. Graphs, Diffraction patterns. 48 ref.--AA